AN ECONOMIC STUDY OF SUPPIY RESPONSE OF CORN CROP IN IRAQ BY USING AUTOREGRESSIVE DISTIRBUTED LAG MODELS (ARDL) FOR THE PERIOD1970-2014 - & Al Hani, Baldawi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Corn is one of the major crops of industrial and food importance. Corn is mainly grown for domestic consumption of the production of corn flakes, starch export, and corn seeds are used for baking when mixed with wheat flour, The average production and cultivated area of the corn crop in Iraq for the period (1970-2014) reached (210042.431 tons), (342,974,866 acres), respectively, It accounts for (8%, 3%) of the total production and areas cultivated with grain crops. The productivity rate was (555.7 kg / Acres), which accounted for 32% of the grain production in Iraq, Which is a good percentage after the yield of the bear compared to the yield of wheat and barley. The objective of this study was to measure the effect of price and non-price changes on the area planted with corn crop for the period (1970-2014) by using ARDL models to test joint integration and estimate the short- and long-term equilibrium relationship. The main factors were identified for the respond to the presentation of the area cultivated with the wheat crop and there are (the area planted with wheat in Iraq for the previous year (acres), Price of wheat crop (Dinar / ton), The price of barley crop (Dinar / ton), Water discharge of tigirs and Euphrats Rivers (billion cubic meters), Productive risk, Price risk, dummy variable represented by years of war), The stability of the time series was revealed and it was obvious that there is instability of the time series of the area variable for the previous year, the price variable of the corn crop, the variable price of the competing crop and the price risk. After taking the first difference for those variables it became clear that this produce a stability in them without taking the second difference. Its noted that all transactions in the short term were highly significant except for the variable price of corn crop was not significant, The error correction coefficient (-1.09) is negative as expected and very significant, this means that there is a long-term equilibrium relationship between the economic variables studied in the short term, the value of the error correction parameter (λ) means that there is a high speed in adjusting the short-term imbalance in the area planted with corn crop in the previous period (t-1) that can be corrected in the current period (t) In the direction of the long-term equilibrium relationship due to any (shock )or change in explanatory variables, where (λ) represents the speed or rate of correction of the error in the direction of return to the equilibrium situation and means that the area planted with corn crop takes about nine months or (0.91) year In the direction of its equilibrium value after the impact of any shock in the model due to the change in the explanatory variabless.